The Judicial Power And Constitutional Government: Convergence And Divergence In The Australian And Malaysian Experience - Lee, HP (Journal of Malaysian and Comparative Law, 2005)
Tun Mohamed Suffian, described by Tun Mohamed Dzaiddin as "a person of unshakable principles", made an outstanding contribution to his nation. He occupied with distinction the office of Lord President (no "Chief Justice") of the Federal Court from 1974 to 1982. As the leader of the "least dangerous" branch of government, he guided the Malaysian judiciary along a path rigorous judicial integrity and independence.